Synthesis, spectral characterization and biological activities of Organotin(IV) complexes with ortho-vanillin-2-hydrazinopyridine (VHP) - Norrihan, Sam; Md. Abu, Affan; Abdus, Salam; Mohd Razip, Asaruddin (OJIC, 2012)
Five new organotin(IV) complexes of ortho-vanillin- 2-hydrazinopyridine hydrazone with formula [RnSn- Cl4–n(VHP)] [R = Me2, n = 2 (2); R = Ph2, n = 2 (3); R= nBu2, n = 2 (4); R = nBu, n = 2 (5) and R = 1, n = 0 (6)] have been synthesized by direct reaction of orthovanillin- 2-hydrazinopyridine hydrazone [(VHP), (1)], base and organotin(IV) chloride(s) in absolute methanol. The hydrazone ligand [(VHP), (1)] and its organotin( IV) complexes (2-6) have been characterized by UV-Visible, FT-IR and 1H NMR spectral studies. Spectroscopic data suggested that in the complexes (2-4), the ligand (1) acted as a neutral bidentate ligand and is coordinated to the tin(IV) atom via the azomethine nitrogen and pyridyl nitrogen atoms, whereas the ligand (1) acted as a uninegative tridentate ligand and coordinated to the tin(IV) atom through phenolic- O, azomethine-N and pyridyl-N atoms in complexes (5-6). The toxicity of the ligand (1) and its organotin (IV) complexes (2-6) were determined against Artemia salina. Organotin(IV) complexes showed moderate activity against Artemia salina. The ligand (1) and its organotin(IV) complexes (2-6) were also tested against four types of bacteria namely Bacillus cereus, Staphylococcus aureus, Escherichia coli and Enterobacter aerogenes. All organotin(IV) complexes and the free ligand (1) showed better antibacterial activities against bacteria. Among the organotin(IV) complexes (2-6), diphenyltin(IV) complex (3) showed higher activity against the four types of bacteria.